The Effectiveness of Interventions to Address Health Inequalities During Pregnancy: A Review of Relevant Literature - Hallam, Angela (Current Women's Health Reviews, 2008)
Introduction: This paper presents a summary of what is known about the effectiveness of interventions to address health inequalities during pregnancy. The research was carried out as part of a wider review of the literature relating to interventions to address inequalities in the early years. This contributed to the work of Scotland's Ministerial Task Force on Health Inequalities, which reported in June 2008. Objectives: The objectives of this article are to provide a broad summary of the evidence base; highlight the known effectiveness of specific interventions; and identify gaps. Methods: The review is based on analysis of data from publications/work in progress recommended and/or produced by the Scottish Government, its agencies and those conducting relevant research within universities and other organisations across Scotland. Findings: Evidence supports school and community-based sex and relationship education as effective in averting pregnancy at a young age. During pregnancy, intensive and direct interventions, such as vouchers and provision of food, have a greater chance of improving nutritional status than simply providing advice and information. Multi-faceted initiatives (information, advice and counselling) are more likely to be effective in addressing smoking cessation than a single service. Antenatal care programmes may improve outcomes for both teenage mothers and their infants, but little research has been carried out on the content of antenatal classes, and there is little evidence relating to Scotland or to the rest of the UK. Conclusions: There is good evidence to show the effectiveness of a range of initiatives, both at the level of the population and the individual, although the most vulnerable groups are inevitably the most difficult to engage. Tapping into the popularity of computer games and other technological approaches may help young people engage with issues relating to relationships and the care of young infants, although initiatives have yet to be evaluated in the UK. Families who are hard to reach by traditional services may feel more comfortable receiving antenatal home visits from volunteers within their own community, although it is important that such volunteers receive appropriate training and support.
Keywords: vouchers